Study of plant emergence by different cultivation - Máthé-Gáspár, Gabriella; Rátonyi, Tamás (Acta Biologica Szegediensis, 2008)
Field emergence of different crops significantly varies under Hungarian ecological conditions. Tillage systems may strongly affect the germination environment of seeds by changing temperature and moisture of the topsoil, seed-soil contact and the amount of crop residues. The objective of this experiment was to study the effect of soil cultivation on maize germination. Methods of soil cultivation were: conventional tillage (winter ploughed soil), spring tillage, conservation tillage (spring disk harrowing). Spring was particularly dry. Bulk density and water content in case of winter ploughed soil was higher and the placement of plant residues was lower compared to spring tilled soil. The highest germination percentage of maize was observed after winter tillage, the lowest was after spring disk tillage. The cultivation had a higher effect on germination than the differences of soil moisture or soil compaction in itself. Plant residues got into greater depths in the ploughed treatment and ploughing reduced the number of weed seedlings. In the effect of cultivation the changes of multiple soil conditions were cumulated. Results suggest an important effect of cultivation method on bulk density, on water holding capacity parameters of soils and finally on seedling emergence.